Biodegradable Poly (Butylene Adipate‐Co‐Terephthalate) and Thermoplastic Starch Sustainable Blends Modified by Epoxy‐Terminated Hyperbranched Polyester with Excellent Mechanical Properties and High Transparency. (13th January 2023) - Guo, Maolin; Jin, Yujuan; Han, Xiaolong; Sun, Jianjian; Yuan, Jinglan; Tian, Huafeng
Abstract: A kind of fully biodegradable poly (butylene adipate‐co‐terephthalate) (PBAT)/thermoplastic starch (TPS) blend is prepared by melt processing with epoxy‐terminated hyperbranched polymer (EHBP) as a modifier. The effect of EHBP on the performance of PBAT/TPS blends is investigated. The terminal epoxy group of EHBP can react with the hydroxyl and carboxyl groups of PBAT and TPS, which increases the compatibility of PBAT and TPS. Meanwhile, the formation of hydrogen bonds and chain entanglement increases the adhesion between PBAT and TPS, which improves the mechanical properties of the blends. When the content of EHBP is 3 phr, the elongation at break of TPS/PBAT/EHBP blends increases by 28.99% (from 260.32% to 335.79%) and the impact strength increases by 215.78% (from 9.38 to 29.62 kJ m −2 ). Scanning electron microscopy (SEM) images show that the compatibility of PBAT/TPS/EHBP blends gradually improves with the addition of EHBP. UV results show that the transparency of PBAT/TPS blends is greatly improved by the addition of EHBP, which also indicates the compatibility of PBAT and TPS is improved by the addition of EHBP. It provides an effective way to prepare PBAT blends with excellent properties through, an environmentally friendly and low‐cost processing method. Abstract : In this work, the epoxy‐terminated hyperbranched polymer EHBP is synthesized and applied to the modification of PBAT/TPS blends. With the addition of EHBP, the compatibility and toughness of PBAT/TPS blends are improved.